ANALYSING UTTERANCES ON MOVIE BY USING THE GRICEAN MAXIM - Ana Fergina (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2011)
Expressing what we want to say to other speaker can be done by saying directly and indiectly. This can be successful or not. Many women, hovewer, tend to fail to use directness in certain conversation. This study was to investigate whether women flout Grice maxim in Cooperative Principle . The study analyses uttetances of speakers taken from movie. The study suggested that interlocutors follow Cooperative Principle in the conversation. However, some utterances do not show this principle due to some factors; for example chance to speak and politeness.